Pengaruh Iklan, Kredibilitas Endorser, Daya Tarik Iklan Terhadap Minat Beli Iphone (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Bisnis Universitas Islam Malang) - Rafi, Basyaruddin Faizal; Wahono, Budi; Basalamah, Muhammad Ridwan (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This thesis is entitled "The Influence of Advertising, Endorser Credibility, Advertising Appeal on iPhone Purchase Interest" Case study on students of the Faculty of Economics and Business class of 2020 at the Islamic University of Malang. The purpose of this study is to analyze the influence of advertising, endorser credibility, advertising appeal simultaneously and partially on iPhone purchase interest. This study uses an explanatory research method with a quantitative approach. This sample collection uses purposive sampling and gets 85 samples. This data collection uses a questionnaire method that is distributed offline and online via google forms and questionnaire paper. The simultaneous results of this study are that advertising, endorser credibility, advertising appeal have a significant effect on iPhone purchase interest. The partial results of this study are that advertising has a significant effect on purchase interest, endorser credibility has a significant effect on purchase interest, and advertising appeal has a significant effect on iPhone purchase interest. Keywords: Advertising, Endorser Credibility, Advertising Appeal, And Purchase Interest.